STRATEGI PENDIDIKAN KEWIRAUSAHAAN DI SEKOLAH DASAR ALAM MUHAMMADIYAH BANJARBARU - Muhammad Rifqi Hidayat; Rusdiana Rusdiana; Parman Komarudin (Departemen Ilmu Administrasi Bisnis, Fakultas Ilmu Sosial dan Ilmu Politik, UNPAD, 2021)
The purpose of this research is to examine methods of entrepreneurship education at Elementary School of Alam Muhammadiyah Banjarbaru, and to analyze the supporting and inhibiting factors. This is a qualitative field research using the interpretive approach to achieve the first goal, and the SWOT analysis (Strength, Weakness, Opportunity, and Thread) to achieve the second goal. The data in this research collected by the research team through interviews with the teachers, observations on entrepreneurial education activities that schools do, and questionnaire for the analysis of supporting and inhibiting factors. The results showed that Elementary School of Alam Muhammadiyah Banjarbaru held a